A new pathophysiology in heart failure patients. Issue 12 (12th August 2020) - Sciomer, Susanna; Rellini, Carlotta; Agostoni, Piergiuseppe; Moscucci, Federica
Abstract: In the treatment of patients with severe heart failure, left ventricle assist device plays an important role, especially as a destination therapy. Nevertheless, even in successful cases, patients' progressive weaning is rarely taken into consideration. The recovery of more physiological circulation conditions is not a main goal. This hypothesis is discussed in this article.